An adaptive redundant reservation admission in virtual cloud environment. (2019) - Liu, Dongbo; Li, Yongjian
In cloud platforms, resource reservation service is an effective approach to providing desirable quality of service (QoS) for user applications. However, conventional reservation service might result in lower resource utilisation and higher rejection rate if it is excessively applied. In this paper, we proposed an adaptive redundant reservation strategy, which uses overlapping technique to implement reservation admission and enable resource providers dynamically determine the best redundant degree at runtime. By overlapping a new reservation with an existing one, a request whose reservation requirements can not be satisfied in a traditional way might be accepted. Also, by dynamically determining the best redundant degree, the proposed strategy can obtain optimal trade-offs between performance and reliability for cloud platforms. Experimental results show that the proposed reservation service can bring about remarkably higher resource utilisation and lower rejection rate when using redundant reservation service at the price of a slightly increasing of reservation violations.